KEPASTIAN HUKUM KEPEMILIKAN PASAR TRADISIONAL MILIK PIHAK SWASTA TERKAIT DENGAN PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM. - Rustandi, Riki; Yuhelson, Yuhelson; Kencanawati, Erny (SENTRI: Jurnal Riset Ilmiah, 2023)
Land as a gift of God Almighty is a natural resource which is indispensable man for earning his living. Land has economic value as well in addition to social functions, One of the common interest of traditional market. To build a traditional market of land needed to be done by way of land acquisition, which is a legal act by the government to obtain by way of land acquisition, which act by the government for specific interest by providing compensation to landowners according to the procedure in the act. Development of common interests, are owned by the government, while it must be done by the private sector by a treaty. If the public interest is ultimately owned by either private ownership or management then it isn’t regulated in accordance with Law Number. 2 of 2012 on Land Procurement for Development for Public Interest. The method used in this research is normative juridical research, specifically a library law research or secondary data with primary, secondary and tertiary legal sources. As for the research approach used in this case the legislation relating to land acquisition and the method of collecting the legal materials are carried out by identifying and taking an inventory of positive law, journals and other legal sources. The method used in analyzing the legal materials (interpretation) is to get views on the public interest is ultimately owned by either private ownership or management. to get legal certainty and legal construction method. From the research results can be obtained that District Government Karawang after Turi Tempuran land procurement market is not accompanied by management well, so when the market was transferred by the village government to the private sector can’t by a treaty. This causes the market being owned and managed by private parties